A Descriptive Study On Teaching Recount Text At The Eight Grade Of SMP N 2 Jenawi, Karanganyar - Kusumawati, Ratih, Dr. Dwi Haryanti, M.Hum, Drs. Djoko Srijono, M.Hum (2014)
This study aims at describing the method used by the teacher in teaching recount text at the eight grade of SMP N 2 Jenawi, Karanganyar and to describe problem faced by the students in understanding reading recount text. This is a descriptive qualitative research. The researcher collected the data by observing the English class and interviewing the teacher. The data include field note of observation, interview script, and syllabus. While, the methods of collecting the data are observation, interview, and document. The technique used in analyzing data is as follows collecting the data of the observation and interviewing, analyzing the data from the result of observation and interview, and concluding the result and giving suggestion. The results of the research shows that the first, the method used by the teacher in teaching recount text to the eight grade of SMP N 2 Jenawi, Karanganyar in teaching-reading. The objective of teaching English at junior high school is by studying English students are expected to have comprehension in reading by topics of recount text. The material for teaching reading is recount text. Recount text is a text which retells events or experiences in the past. The teacher used the media related with the material. In process of teaching, the teacher gave the opportunities for the children to participate in activities in the class. So the objective of teaching English is achieved. In the evaluation, the teacher used the standardized test and daily test. Standardized test is the test made by the government to measure achievement at student nationally. The daily test is a test made by the teacher to measure the student ability. In daily evaluation the teacher give the daily assignment, homework and the standardized test will be conducted at the end semester. The problem faced by the students in reading comprehension can be divided into three; (a) Punctuation problem makes the students' difficulties in finding the main idea of recount text. (b) The students have difficulties in translating the word from English into Indonesian and Indonesian to English. (c) Most of the students have difficulties in arranging the sentence correctly because the students get problems arranging words become good sentences.